Information and Post-Harvest Food Safety Handling Practices among Pumpkin Farmers in Ikwo Local Government Area of Ebonyi State, Nigeria (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The study assessed information and post-harvest food safety handling practices among pumpkin farmers in Ikwo Local Government Area, Ebonyi State. The specific objectives of the study were to: assess post-harvest food safety handling practices, identify the sources of information on post-harvest food safety handling practice and identify the constraints faced by small-holder pumpkin farmers in post-harvest food safety handling practices. Multi-stage sampling procedure was employed for the selection of the respondents while a well-structured questionnaire was used to collect data. Frequency, percentage, mean and factor analysis were used for data analysis with the help of SPSS. The study found that 59.7% of pumpkin farmers were females, the mean age was approximately 47 years, 41.7% obtained primary education, 59.9% were members of social organizations. Furthermore, the study found that 68.75% of the post-harvest food safety handling practices of the respondents were incorrect. Fellow farmers, television and friends/neighbours were among credible sources of information used by the respondents. Volume/income/sensitization, weak institution/prices/ health officers/knowledge were among constraints hindering post-harvest food safety handling. Relevant authorities should ensure that pumpkin farmers have access to training and adequate supports on post-harvest food safety handling practices to prevent contamination of pumpkin products that will promote public health.
Keywords: Contamination; Consumption; Handling; Health; Production